INTERVENTION AND EVALUATION OF THE MOTIVATIONAL CLIMATE TRANSMITTED BY A BASKETBALL COACH - Cristina Conde (Revista de Psicología del Deporte, 2009)
Coaches are reference models for youth athletes and have a high degree of influence over them, and thus a suitable education is important. Therefore, the purpose of this study was to assess how a basketball coach progresses in the transmission of a task climate during his basketball training sessions, after participating in a reflective educational program focused on the coach's actions. In this study, a basketball coach and the two teams that he coached participated. All the players were between 14 and 15 years of age. The behavior of the coach was analyzed through an adaptation of the Coaching Behavior Assessment System (CBAS) (Smith, Smoll, & Hunt, 1977). The observational analysis was carried out by the research team, who was previously trained. Six sessions of observation were carried out, and inter- and intraobserver reliabilities of 97.6% were obtained. During three months, the coach participated in an educational program consisting of six supervised cycles in which the premises established by Ames (1992) with the abbreviation TARGET were followed, in order to transmit a task climate during his coaching sessions. The results demonstrate a progression in the climate that was transmitted by the coach. In the first training session, the proportion of the climate that he transmitted as task was 65.67% and the ego climate was 34.43%, while in the penultimate training session it was 85.11% for task versus 14.89% for ego, and this was the session with the greatest proportion of transmitted task climate. These data demonstrate that as the educational program was applied, the coach progressively increased the task climate during the training sessions (Sousa, Cruz, Torregrosa, Vilches, & Viladrich, 2006). It can be concluded that with the application of an educational program focused on the coach's own actions, the climate oriented to task improved in training sessions.